(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2024)
In the context of modern education, the integration of technology plays a pivotal role in enhancing practical skills and knowledge acquisition. This paper delves into the significance of Computer Numerical Control (CNC) technology within the domain of woodwork technology at tertiary institutions using a quasi-experimental design involving 47 participants drawn from the National Institute of Construction Technology and Management, Uromi, Edo State, Nigeria. The study was structured as an educational design experiment using simulation modeling to teach woodwork concepts. An experiment of two equivalent groups was designed; one was the experimental group, and the other was the control group. The same project was given to the first (the experimental group) and second (the control group) groups using a simulation program and the traditional method. Simulation modeling proved to be an efficient method for enhancing woodwork skills. The results show that students used simulation programs to demonstrate more profound learning and understanding of the design concepts than the traditional method.